2008
DOI: 10.1038/onc.2008.83
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic silencing of AXIN2/betaTrCP and deregulation of p53-mediated control lead to wild-type β-catenin nuclear accumulation in lung tumorigenesis

Abstract: b-catenin accumulation is often found in lung tumors, but only a few patients have mutations in b-catenin gene. In addition, activated p53 downregulates b-catenin. Therefore, we postulated that alteration of the degradation complex AXIN2 (axis inhibition protein 2) and betaTrCP (b-transducin repeat-containing protein) and p53 regulation could result in b-catenin protein accumulation in lung cancer. Using the immunohistochemical and sequencing analyses, we found that patients with b-catenin accumulation without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
37
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 30 publications
(34 reference statements)
7
37
0
Order By: Relevance
“…On the one hand, these findings are consistent with our previous observation that not all genes suppressed by polycomb-mediated methylation are necessarily maintained by promoter DNA methylation (24). On the other hand, the observation that AXIN2 repression in HCC was associated both with H3K27 and DNA methylation, as reported in other cancers (43), supports the notion that reversible polycomb-mediated repression can result in stable silencing (44)(45)(46). Collectively, the differential patterns of epigenetic marks might reflect the independence and interplay of gene silencing mechanisms in the Supplementary Table S5.…”
Section: Discussionsupporting
confidence: 82%
“…On the one hand, these findings are consistent with our previous observation that not all genes suppressed by polycomb-mediated methylation are necessarily maintained by promoter DNA methylation (24). On the other hand, the observation that AXIN2 repression in HCC was associated both with H3K27 and DNA methylation, as reported in other cancers (43), supports the notion that reversible polycomb-mediated repression can result in stable silencing (44)(45)(46). Collectively, the differential patterns of epigenetic marks might reflect the independence and interplay of gene silencing mechanisms in the Supplementary Table S5.…”
Section: Discussionsupporting
confidence: 82%
“…The application of β-catenin immunohistochemistry has been proposed in the differential diagnosis of PB, the blastomatoid variant of carcinosarcoma, and other types of NSCLC 12 24. However, a similar expression pattern of β-catenin can be seen in PBs and in NSCLCs and CTNNB1 mutations do not necessarily result in nuclear translocation of β-catenin 22. Therefore, our data suggest that one should perform CTNNB1 sequencing rather than β-catenin immunohistochemistry in the differential diagnosis of PB and NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, low βTrCP expression may result from the low levels of its substrates (28), such as phospho-β-catenin and SNAI1, in SLIT2 knockdown cells. Our previous study showed that knockdown of the βTrCP gene increases β-catenin expression in lung cancer cells (29). Relevantly, He and colleagues (30) found that knockdown of βTrCP accelerates cell invasion of lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%